Assessment of tetracycline and fluoroquinolones residues in pork in Hung Yen province - Dang Xuan Sinh; Phuc Pham Duc; Luu Quoc Toan; Nguyen Mai Huong; Trinh Thu Hang; Nguyen Hung Long; Hung Nguyen-Viet (2014)
Antibiotic residues in foods do not only affect consumers and public health but also affect the livestock industry. We studied the prevalence and concentration of Tetracycline and Fluoroquinolones groups in pork in Hung Yen. A total of 160 pork samples were collected and analyzed using HPLC and ELISA techniques. Results showed that 13/160 (12,31%) samples were positive to Tetracycline group, while Fluoroquinolones group was not found. The residual prevalence of Tetracycline, Oxytetracycline and Chlotetracycline were 3,75, 2,5 and 1,88%, respectively. An average residue concentration of Tetracycline group in pork was 133,72 (50,25-382,9) µg/kg. Compared with the maximum residual limits, two samples exceeded permissible standards of Vietnam and 6 samples exceeded the permitted level of the FAO/WHO and the European Food Safety Authority (EFSA). These findings underlines the situation and trends of antibiotic residues in Hung Yen in particular and in Vietnam in general. Therefore, the monitoring and management of safe and properly using antibiotics in animal husbandry and veterinary needs to be improved.